The cifra delle caselle a XVI Century superencrypted cipher. Issue 1 (2nd January 2020) - Bonavoglia, Paolo
Abstract: Superencryption was widely introduced after the XVIII Century for improving the security of codes; the basic idea is of encrypting a second time an already code-encrypted text, with a different cipher, usually a MASC or Vigenère cipher. But now in the State Archive of Venice, a few XVI Century superencrypted messages were found, using the so-called cifra delle caselle, first with a small two-digit nomenclator, then superencrypted with a grata a 24 × 26 grid of numbers.